PENGEMBANGAN MEDIA GAME QUIZ INTERAKTIF BERBASIS MODEL ADDIE PADA MATERI PENJUMLAHAN DAN PENGURANGAN KELAS II SD : Penelitian Skripsi - Nuraini, Putri; Zahrani Susilo, Claudya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study seeks to create interactive quiz game media with Canva, employing the ADDIE paradigm for addition and subtraction content aimed for second-grade primary pupils, and to evaluate its validity and usability. This study is a research and development endeavor using the five steps of the ADDIE model: analysis, design, development, implementation, and evaluation. The study participants were 15 second-grade pupils from SDN Pundong 2 Jombang. The study tools included a media expert validation form and a student practicality questionnaire on a four-point Likert scale (1–4). The data were examined using qualitative and quantitative descriptive methods by calculating the feasibility percentage. The validation findings from three media specialists yielded an average percentage of 85.56%, categorizing it as very practical. The results of the practicality exam, derived from student replies, indicated an average percentage of 75% within the practical area. Indicators of motivation and learning engagement achieved a notable 83%, suggesting that gaming features may enhance students' active involvement in mathematics education. The built interactive quiz game is deemed very realistic and useful for teaching addition and subtraction to second-grade primary students. This medium is anticipated to serve as an alternative to digital learning innovations that enhance students' attention, engagement, and educational experiences in a more pleasurable and significant manner.